2020
DOI: 10.22437/edufisika.v5i02.10431
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Fisika Siswa

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran discovery learning terhadap hasil belajar fisika siswa. Subjek penelitian adalah 30 siswa kelas X Madrasah Aliyah Muhammadiyah Riung Tahun Pelajaran 2019/2020. Jenis penelitian ini yaitu kuantitatif. Desain penelitian Ex-post facto yang bersifat kausalitas. Data yang diperoleh adalah data hasil belajar siswa pada pelajaran fisika. Analisis data yang dilakukan adalah uji normalitas dan uji t. Hasil uji hipotesis, diperoleh data t (terhitung) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…This low learning outcome is used as a strong indicator so that there is the influence of the discovery learning model on students' science learning outcomes. This is supported by research (Wahyuni et al, 2020) which found that there was an effect of the discovery learning model on the physics learning outcomes of class X students at Madrasah Aliyah Riung.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This low learning outcome is used as a strong indicator so that there is the influence of the discovery learning model on students' science learning outcomes. This is supported by research (Wahyuni et al, 2020) which found that there was an effect of the discovery learning model on the physics learning outcomes of class X students at Madrasah Aliyah Riung.…”
Section: Introductionmentioning
confidence: 65%
“…The obstacle faced by researchers is the lack of computer facilities so that in learning students are divided into groups. In terms of previous research Wahyuni et al, (2020) with the title the effect of the discovery learning model on student physics learning outcomes. Shows the influence of the discovery model on student learning outcomes at Madrasah Aliyah Muhammadiyah Riung.…”
Section: Figure 1 Graph Of Students' Thinking Abilitymentioning
confidence: 99%
“…Hasil ini sejalan dengan penelitian yang dilakukan oleh (Wahyuni et al, 2020) yang mendapatkan kesimpulan bahwa discovery learning memberikan pengaruh yang signifikan terhadap hasil belajar peserta didik. Pengaruh tersebut berupa kenaikan nilai hasil belajar peserta didik yang cukup signifikan jika dibandingkan dengan hasil belajar peserta didik kelas kontrol.…”
Section: Pembahasanunclassified